2016
DOI: 10.1149/07204.0335ecst
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antiphase Domain Boundary Annihilation Rate in GaAs on Si(001) and the Influence of MOCVD Growth Temperature

Abstract: The effect of growth temperature on the annihilation of antiphase domain boundaries (APBs) in GaAs grown on 300 mm Si(001) wafers via an industrial III-V metal organic chemical vapor deposition (MOCVD) tool is examined. Samples were grown with identical low temperature nucleation layers to set the APB density before growth of bulk layers at varied temperature. The APB annihilation rate with respect to GaAs film thickness is determined by profiling the APB density in the samples as a function of depth using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[41,48] It was widely assumed that the stoichiometric {110} APBs, that run perpendicular to the interface, are the more common. [48][49][50] Therefore, in order to reduce the number of emerging APBs, some studies aimed at promoting of the generation of tilted APBs. [35] Moreover, in 2020, K. Li et al [48] indicated a correlation between the organization of the Si surface and the APBs annihilation.…”
Section: Introductionmentioning
confidence: 99%
“…[41,48] It was widely assumed that the stoichiometric {110} APBs, that run perpendicular to the interface, are the more common. [48][49][50] Therefore, in order to reduce the number of emerging APBs, some studies aimed at promoting of the generation of tilted APBs. [35] Moreover, in 2020, K. Li et al [48] indicated a correlation between the organization of the Si surface and the APBs annihilation.…”
Section: Introductionmentioning
confidence: 99%
“…From the film growth start point (Si/GaAs interface) to the end point (GaAs top surface) the APB density decreased gradually by several times in the baseline process shown as the black line in Figure 2. With 80 °C higher growth temperature (blue line in Figure 2), the APB density decreased rapidly by 3 orders of magnitude from the similar starting APB density (2). The APBs can be self-annihilated and the process is thermally activated.…”
Section: Resultsmentioning
confidence: 94%
“…GaAs films were grown with the same pre-cleaning and thickness (~800nm) but different temperatures. The APB density depth profile was measured by step etching and decoration (2). From the film growth start point (Si/GaAs interface) to the end point (GaAs top surface) the APB density decreased gradually by several times in the baseline process shown as the black line in Figure 2.…”
Section: Resultsmentioning
confidence: 99%